Pa pēdām Aristotelim - Tomsone, Paula; Livdāne, Sarmīte; Latvijas Universitātes Muzejs (My University, 2019)
Virtuālā izstāde "Pa pēdām Aristotelim" veltīta jaunā studiju gada sagaidīšanai un vēsturiskam atskatam par studentu svētkiem "Aristotelis". Izstādē apskatāmas fotogrāfijas, kurās attēlota svētku gaita no to rašanās līdz pat mūsdienām, kā arī informācija par svētku dibināšanu un svētku norisi.

The virtual exhibition "In the Footsteps of Aristotle" is dedicated to welcoming the new academic year and a historical review of the student festival "Aristotle". The exhibition includes photographs depicting the course of the festival from its inception to the present day, as well as information about the establishment and course of the festival.
In the footsteps of Aristotle
Keywords: Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education; Aristotelis - svētki; Latvijas Universitāte; studenti; tradīcijas; Aristotle - celebration; University of Latvia; students; traditions; fotogrāfijas; photos